Penal extractivism: A qualitative study on punishment and extractive industries in Peru - (:unkn) unknown (SAGE Publications, 2024)
This article introduces the concept of penal extractivism in the punishment and society literature. We define penal extractivism as the punitive strategies that a state implements to safeguard extractive industries from citizens’ contention. This conce...
Keywords: Extractivismo; Sistema penal